Comparison of direct oral anticoagulants to vitamin-K antagonists as treatment for leaflet thrombosis after Transcatheter Aortic Valve Implantation (TAVI). (14th October 2021) - Ferstl, P; Marwan, M; Achenbach, S; Bittner, D O
Abstract: Introduction: Leaflet thrombosis can occur following transcatheter aortic valve implantation (TAVI). While a frequent finding in post-TAVI CT scans, leaflet thrombosis is usually clinically silent and the decision to initiate anticoagulation depends on clinical considerations. Best treatment is unknown. We compared the effectiveness of direct oral anticoagulants (DOAC) and vitamin K antagonists (VKA) to resolve leaflet thrombosis in patients with serial CT imaging following TAVI. Methods: Consecutive TAVI patients who had undergone routine follow-up cardiac CT after TAVI procedures were screened for inclusion in this analysis. A total of 44 patients diagnosed with leaflet thrombosis and available follow-up CT after anticoagulation therapy were identified. Leaflet thrombosis on cardiac CT was defined as presence of hypoattenuated leaflet thickening with or without leaflet motion restriction, as previously described. The indication and type of anticoagulation was according to physician discretion. We compared patients on DOAC with patients on VKA therapy for the resolution of leaflet thrombosis. Results: Mean age of the 44 patients was 80±6 years (59% men), and the median time interval from TAVI to index CT was 107 days (IQR: 91–189 days). Overall, 39 patients (90%) showed resolution of leaflet thrombosis with anticoagulation therapy, whereas leaflet thrombosis persisted in 5 patients (10%). Resolution of leaflet thrombosis was seen in 26 out of 30 (87%) patients receiving VKA and in 13 out of 14 (93%) patients receiving DOAC, respectively. Groups did not differ regarding age (p=0.97), cardiovascular risk factors (all p>0.1), creatinine levels (p=0.19) TAVI prosthesis type (p=0.54) and size (p=0.66). Also, no difference existed for duration of anticoagulation (median 103 vs. 110 days; p=0.76). The relative risk reduction for persisting leaflet thrombosis using DOACs was 46% in comparison to VKA, however with no statistical significance due to the limited number of patients (p=0.55). Conclusion: Anticoagulation therapy resolves leaflet thrombosis after TAVI in the majority of patients. In our exploratory analysis, direct oral anticoagulants seem to be an effective alternative to vitamin-K antagonists. This result is hypothesis generating and needs to be confirmed in larger prospective trials. FUNDunding Acknowledgement: Type of funding sources: None.